A review of soldier beetles of the genus Podistra Motschulsky, 1839 (Coleoptera: Cantharidae) of the Greater Caucasus, with the description of two new species - Kazantsev, S.v. (Zootaxa, 2023)
Two new species of soldier beetles of the genus Podistra Motschulsky, 1839 are described from the vicinity of Mount Elbrus, Caucasus: P. (s. str.) elbrusensis sp. nov. and P. (s. str.) davidyani sp. nov. The total number of Podistra known in the Greater Caucasus is thus raised to seventeen. It is noted that, unlike other cantharids, most species of Podistra of the area are flightless and have reduced elytra either in females or in both sexes. Correlation between altitude and elytral length in Podistra, as well as distribution of the genus in the Greater Caucasus is discussed. A key to all species of this mountain range, with illustrations and a distribution map are provided.